European cities and towns, 400-2000 - Clark, Peter, 1944- (Oxford Univ. Press, 2009)
Examines and explains the waves of urbanization across Europe from the fall of the Roman empire to the dawn of the 21st century, covering the whole of Europe, north and south, east and west, and looking at urban trends, the urban economy, social developments, cultural life, and governance. - ;Since the Middle Ages Europe has been one of the most urbanized continents on the planet and Europe's cities have firmly stamped their imprint on the continent's economic, social, political, and cultural life. This study of European cities and towns from the fall of the Roman Empire to the present day loo.